Blood arsenic levels and the risk of familial breast cancer in Poland. Issue 10 (26th August 2019) - Marciniak, Wojciech; Derkacz, Róża; Muszyńska, Magdalena; Baszuk, Piotr; Gronwald, Jacek; Huzarski, Tomasz; Cybulski, Cezary; Jakubowska, Anna; Falco, Michał; Dębniak, Tadeusz; Lener, Marcin; Oszurek, Oleg; et al.
Abstract : Arsenic is recognized as a potent carcinogen at high concentrations, but the relationship between environmental arsenic and breast cancer risk has not well been studied. Most research has focused on the effect of arsenic in populations with high endemic exposure, and not in populations with arsenic levels within normal limits. We sought to determine if blood arsenic levels predict the risk of breast and other cancers risk among women in northern Poland. The cohort consisted of 1, 702 healthy women, aged 40 and above, identified between 2010 and 2017. Blood arsenic level was determined by inductively coupled plasma mass spectrometry. After an average of 4.5 years of follow‐up (range 0.7–7.3 years), there were 110 incident cases of cancer diagnosed in the cohort, including 68 cases of breast cancer. Women in the highest quartile of arsenic had a highly significant 13‐fold increased risk of developing breast cancer, compared to women in the lowest quartile (hazard ratio [HR] = 13.2; 95% confidence interval [CI] 4.02–43.0). Results were similar for arsenic and all incident cancers (HR quartile 4 vs . quartile 1 = 13.3; 95% CI 4.78–37.0). If confirmed, our study suggests that the blood arsenic level may be a useful predictive marker of cancer risk in women. Abstract : What's new? Arsenic has long been recognized as a potent carcinogen at high concentrations. But can it affect cancer risk at "normal, " environmental concentrations? In this Polish study, the authors found that women whose blood levels of arsenic were in the highest quartile had a 13‐fold increased risk of developing breast cancer, compared to women in the lowest quartile. If confirmed in further studies, these results suggests that blood arsenic level may be a useful predictive marker of cancer risk in women.